Legal promotion and propaganda is an important tool of legal education - Abdusalimova Shakhnoza (Peerian Journals Publishing, 2024)
This article highlights the importance of legal promotion and campaigning in the formation of legal education and raising legal literacy among young people and all members of our society.
Keywords: propaganda; legal propaganda; legal education; election campaigns